Development of a real-time reverse transcription recombinase polymerase amplification assay for rapid detection of spring viremia of carp virus. (April 2020) - Cong, Feng; Zeng, Fanwen; Wu, Miaoli; Wang, Jingjing; Huang, Bihong; Wang, Yingying; Wang, Qing; Zhang, Shouquan; Ma, Lei; Guo, Pengju; Zeng, Weiwei
Abstract: Spring viremia of carp virus (SVCV) is a significant pathogenic agent that can cause large-scale outbreaks of spring viremia of carp (SVC) in many types of fish and bring huge economic losses to the aquaculture industry. A simple and convenient detection method is imperative for SVCV diagnosis. In this study, the real-time reverse transcription recombinase polymerase amplification (RT-RPA) assay was developed and validated. Primers and probe targeting the conserved region of M gene were designed and applied to the real-time RT-RPA assay that performed at 39 °C for 20 min. The specificity analysis showed that no cross-reaction with other pathogenic viruses of fish was found, indicating appropriate specificity of the assay. In vitro transcribed RNA standards were used to estimate the sensitivity of the assay and the detection limit was 10 2 copies/reaction. To further evaluate the assay, 65 clinical samples were tested using both real-time RT-RPA assay and real-time RT-PCR method. The same detection results were observed, suggesting the potential application of real-time RT-RPA assay in clinical sample detection. This is the first report on RPA assay for SVCV detection and this new developed assay would be useful in both laboratory and in the field for diagnosis of SVCV. Highlights: A real-time RT-RPA assay was developed and evaluated for rapid detection of spring viremia of carp virus (SVCV). The real-time RT-RPA assay was highly specific and sensitive. The real-time RT-RPA assay was as sensitive as real-time RT-PCR on clinical sample detection.